Management of foliage feeding wheat aphid (Rhopalosiphum padi) through botanicals and biopesticides - Patil, Sanjay Dhondu (Journal of Cereal Research, 2015)
ABSTRACT Field studies were conducted during Rabi 2008-09 to 2011-12 at Agricultural Research Station, Niphad, Maharashtra, India to determine the efficacy of promising entomopathogenic fungi and plant products (extract) for the management of wheat aphids. Metarhizium anisopliae 1.15% WP @ 4g/l recorded minimum (4.99 and 20.67) number of aphids/shoot/plant at 7 and 15 days after spraying. It was at par with Verticillium lecanii 1.15% WP @ 4 g/l at 7 days after sprayingÂ and Verticillium lecanni 1.15% WP @ 4g/l and Beauveria bassiana 1.15% WPÂ @ 5g/l. Metarhizium anisopliae 1.15% WP @ 4g/l recorded highest yield of 45.06q/ha which was at par with Verticillium lecanii 1.15% WP Â @ 4g/l (44.87q/ha), Beauveria bassiana 1.15% WP @ 5g/l (44.78), Neem Seed Extract 5% (43.13q/ha) and Azadirachtin 1500 ppm 3.0 ml/l (42.81q/ha). Lowest yield was observed from untreated control (35.53 q/ha). The additional yield and income over control was highest in Metarhizium anisopliae 1.15% WP @ 4g/l (9.53 q/ha and Rs. 10,950q/ha). The monetary returns, net profit, benefit cost ratio and ICBR were maximum over control in Metarhizium anisopliae 1.15% WP @ 4g/l (Rs.67,718, Rs.41,606, 2.59 & 8.33). It was followed by Verticillium lecanii 1.15% WP @ 4g/l (Rs.67,453, Rs.41,341, 2.58 & 8.